Comparison of C-MAC® Video Laryngoscope and Macintosh Conventional Laryngoscope for Nasotracheal Intubation Convenience in Adult Malay Race Population - Aldy Heriwardito; Rahendra; Ananto Wiji Wicaksono (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif (PERDATIN) / The Indonesian Society of Anesthesiology and Intensive Care (INSAIC), 2021)
Background: Nasotracheal intubation is a widely used airway management method, especially in oral surgeries. Various devices were found to perform intubation techniques, such as video laryngoscopes. C-MAC® video laryngoscope enables better glottis visualization compared to the Machintosh conventional laryngoscope. C-MAC® demonstrates higher success rates of orotracheal intubation especially in difficult airway cases. However, this device has not been commonly used in nasotracheal intubation yet. Methods: A single blinded randomized clinical trial study of 86 subjects were done to compare the use of C-MAC® video laryngoscope and Macintosh conventional laryngoscope with reference to their success rates of intubation and duration of nasotracheal intubation in adult Malay patients. Patients with difficult airway, pregnancy, acute ischemic heart disease, heart failure, second- or third-degree block, uncontrolled hypertension, Guillen Barre syndrome, Myasthenia Gravis, and contraindications to nasotracheal intubation were excluded. Results: C-MAC® demonstrated a higher success rate at first attempt of intubation (RR 1,265, 95% CI (1,084-1,475)) and required a shorter duration of intubation (p value <0.001) compared to the Macintosh conventional laryngoscopes in adult Malay. Conclusion: In adult Malay patients, nasotracheal intubation is better performed with the C-MAC® video laryngoscope compared to the Macintosh conventional laryngoscope. High rate of successful first attempt and shorter duration of the process indicate more convenient and easier intubation.